2020
DOI: 10.1002/anzf.1426
|View full text |Cite
|
Sign up to set email alerts
|

Putting Single Session Thinking to Work: Conceptual, Practical, Training, and Implementation Ideas

Abstract: There is growing pressure on health and welfare services to provide more efficient and effective services. For one thing, the world's ageing population is resulting in increased pressure on healthcare costs and the availability of government funding. At the same time, community expectations of quick and easy access to high-quality clientcentred services is growing. Single session ideas can make a valuable contribution to responding to these somewhat competing factors, by providing a basis for effective, effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Single session therapy (SST) emerged in the field of mental health services over 40 years ago, as an approach to assist with providing targeted care to mental health users, within a shorter time frame, rather than ongoing regular follow‐up therapy (Hoyt et al, 2021; Talmon & Hoyt, 2015; Young, 2020). It was identified that following a single‐session approach, patients could receive meaningful therapeutic change during one consult, and did not always need to attend ongoing follow‐up consultations (Hoyt et al, 2021; Lee & Tratner, 2021; Talmon & Hoyt, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Single session therapy (SST) emerged in the field of mental health services over 40 years ago, as an approach to assist with providing targeted care to mental health users, within a shorter time frame, rather than ongoing regular follow‐up therapy (Hoyt et al, 2021; Talmon & Hoyt, 2015; Young, 2020). It was identified that following a single‐session approach, patients could receive meaningful therapeutic change during one consult, and did not always need to attend ongoing follow‐up consultations (Hoyt et al, 2021; Lee & Tratner, 2021; Talmon & Hoyt, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…By utilising session frameworks, such as SST, families and clinicians can address the family's needs at that point in time in a complete therapeutic session (Hoyt et al, 2021). Furthermore, the impact of one SST can lead to sufficient change to mitigate the need for further appointments (Lee & Tratner, 2021; Young, 2020). SST differs from other approaches as the core principle is that the family is the driver for the session, and the clinician draws on the family's capabilities to facilitate change and develop actions to occur out of the consult (Hoyt et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Development of all online programs includes an evidence enrichment process. For example, the Single Session Thinking and Single Session Family Consultation training programs are regularly updated to align with the latest research findings, advances in practice, and therapeutic knowledge (Hoyt et al, 2020, 2021; McDonald et al, 2021; Rycroft & Young, 2021; Young, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In early psychosis, depression, and bipolar disorders family work of varying intensity has been found to improve clinical outcomes and is strongly recommended in treatment guidelines [ 33 – 35 ]. Even family work via one-off sessions, delivered on an as-needed basis, have been demonstrated to be useful in other serious mental health issues [ 36 38 ].…”
Section: Introductionmentioning
confidence: 99%